INTERDEPENDENSI KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL SERTA PENGARUHNYA TERHADAP KINERJA KEUANGAN - Fong Ida Melinda; Bertha Silvia Sutejo (Journal of Management and Business, 2008)
This research was explaining the influence of managerial ownership, institutional ownership, and the impact to firm performance. We use three stage least square (3SLS) model to test our hypotheses. Sample of the research is all of manufacture companies which of have managerial ownership and institutional ownership and listed on Indonesian Stock Exchange period 1997 -2006. The result was provided that managerial ownership and firm performance has positive influence but not significant. Other evidence is that institutional ownership has significant positive influence to firm performance. The research was proven that managerial ownership and institutional ownership have negative influence. Condition crisis and after crisis has effect to ownership and firm performance. Firm performance does increase when after crisis period opposite that crisis period.